An analysis of case studies for advancing photovoltaic power forecasting through multi-scale fusion techniques - Mawloud Guermoui; Amor Fezzani; Zaiani Mohamed; Abdelaziz Rabehi; Khaled Ferkous; Nadjem Bailek; Sabrina Bouallit; Abdelkader Riche; Mohit Bajaj; Shir Ahmad Dost Mohammadi; Enas Ali; Sherif S. M. Ghoneim (Scientific Reports, 2024)
Abstract Integration renewable energy sources into current power generation systems necessitates accurate forecasting to optimize and preserve supply–demand restrictions in the electrical grids. Due to the highly random nature of environmental conditions, accurate prediction of PV power has limitations, particularly on long and short periods. Thus, this research provides a new hybrid model for forecasting short PV power based on the fusing of multi-frequency information of different decomposition techniques that will allow a forecaster to provide reliable forecasts. We evaluate and provide insights into the performance of five multi-scale decomposition algorithms combined with a deep convolution neural network (CNN). Additionally, we compare the suggested combination approach's performance to that of existing forecast models. An exhaustive assessment is carried out using three grid-connected PV power plants in Algeria with a total installed capacity of 73.1 MW. The developed fusing strategy displayed an outstanding forecasting performance. The comparative analysis of the proposed combination method with the stand-alone forecast model and other hybridization techniques proves its superiority in terms of forecasting precision, with an RMSE varying in the range of [0.454–1.54] for the three studied PV stations.